Large stable deformation of dielectric elastomers driven on mode of steady electric field. (4th April 2017) - Zhang, Junshi; Zhao, Jianwen; Wang, Shu; Chen, Hualing; Li, Dichen
Abstract: Dielectric elastomers (DEs) are capable of large deformation under the actuation of applied voltage and sprayed charge. Actuation of DE under voltage control is prone to electromechanical instabilities, while the DE under charge control always survives from instabilities with sacrificing a large deformation. In this article, a novel actuation mode of steady electric field is proposed. By tuning applied voltage and sprayed charge during viscoelastic creep, an invariable electric field is generated. Such an actuation method can both avoid the occurrence of electromechanical instabilities and guarantee a large deformation in DE actuation.